Tanggung Jawab Perusahaan Asuransi Terhadap Tertanggung dalam Penutupan Asuransinya Melalui Media Internet - Desni Raspita (Universitas Batanghari Jambi, 2021)
In the times, it will affect human civilization, namely the discovery of one technology, namely the internet. Internet technology at this time has developed rapidly so that it becomes the basis for various human lives. The research method used is normative legal research. with insurance responsibilities that are closed conventionally, where the responsibilities of insurance companies both via the internet and conventional have been confirmed in the loss insurance policy and the exceptions that have been agreed upon by both parties at the time of closing the insurance agreement.